Responses to water stress extremes in diverse red clover germplasm accessions - Heslop, Angus D.; Jahufer, Zulfi; Hofmann, Rainer W. (Frontiers in Plant Science, 2023)
Red clover (Trifolium pratense), a key perennial pastoral species used globally, can strengthen pastural mixes to withstand increasingly disruptive weather patterns from climate change. Breeding selections can be refined for this purpose by obtaining an in-depth understanding of key functional traits. Trait responses critical to plant performance under drought and waterlogged conditions in seven red clover accessions were evaluated and compared against white clover in a glasshouse pot trial. Several morphological and physiological traits were identified as key contributors to the different plant coping mechanisms displayed. Under drought, all aboveground morphological traits decreased, highlighted by a 41% decrease in total dry matter and 50% decreases in both leaf number and leaf thickness. An increase in root-shoot ratio indicated a shift to prioritizing root maintenance by sacrificing shoot growth, a trait attributed to plant drought tolerance. Under waterlogging, a reduction in photosynthetic activity among red clover accessions reduced several morphological traits including root biomass, total dry matter, and leaf number. The importance of root morphology for waterlogging was highlighted with low performance of red clover: there was an 83% decrease in root biomass compared to white clover which was able to maintain root biomass and therefore plant performance. This study highlights the importance of germplasm evaluation across water stress extremes to identify traits for future breeding programs.